BUDAYA PATRIARKHI DAN KEKERASAN TERHADAP PEREMPUAN - Israpil, Israpil (LPPI Universitas Al-Qolam Malang, 2018)
Culturally, Indonesian society is indeed very thick with patriarchal customs. Patriarchy is a concept used in the social sciences, especially in Anthropology. The concept of patriarchy and violence against women is the main discussion in this paper. Patriarchal culture has for generations shaped differences in behavior, status and authority between men and women, the distribution of male power has advantages over women in one or more aspects, such as the determination of lineage (exclusive patrilineal descent and carrying a last name), rights of firstborn children, personal autonomy in social relations, and participation in public and political status. Men monopolize all roles. The unequal relationship often creates conflicts within the community, especially conflicts within the household that lead to acts of violence against women.